Minicutting - A powerful tool for the clonal propagation of the selected species of the Eucalyptus hybrid clones based on their pulpwood studies. (November 2019) - Kuppusamy, Sowmya; Ramanathan, Seenivasan; Sengodagounder, Subramanian; Senniappan, Chinnaraj; Brindhadevi, Kathirvel; Kaliannan, Thamaraiselvi
Abstract: In this study, five improved clones of the Eucalyptus hybrid species namely, E.pellita X E.camaldulensis (Clone No.9), E.camaldulensis X E.pellita (Clone No. 21), E.camaldulensis X E.tereticornis (Clone No.4), E.camaldulensis X E. p ellitta (Clone No. 16) and E.tereticornis X E.urophylla (Clone No. 41) were selected. All of these clones had an efficient micropropagation protocol which was already developed and pulping properties were studied earlier. In order to develop these clones in large scale, miniclonal gardens were developed using minicutting technology. The microcuttings derived from these micropropagated plantlets of the five different clones of the Eucalyptus hybrid species were grown on the sand bed. Its growth was found to be efficient through the application of the nutrient solution. Minicuttings were produced from the microcuttings taken from the micropropagated plantlets of these clones. All these clones were found to adapt the minicutting technology which was evident from the statistical analysis of its growth parameters.